The effects of job resourcefulness and customer orientation on performance outcomes: Evidence from Nigeria - Karatepe, Osman M. (My University, 2013)
This study develops and tests a conceptual model that investigates customer orientation as a full mediator of the effect of job resourcefulness on performance outcomes. Data were obtained from a sample of full-time frontline employees in the four- and five-star hotels in Abuja, the capital city of Nigeria. These relationships were tested with path analysis in LISREL 8.30. As hypothesized, job resourcefulness is positively linked to employees' customer orientation. Consistent with the study predictions, customer orientation enhances employees' external representation and service delivery behaviors. However, the results indicate that customer orientation does not significantly affect employees' internal influence behaviors. The results further reveal that customer orientation fully mediates the impact of job resourcefulness on employees' external representation and service delivery behaviors. In other words, job resourcefulness influences such performance outcomes via customer orientation. Managements of the hotels would benefit from the use of effective recruitment and selection techniques to be able to hire employees who can work under resourcedepleted conditions. In addition, managements of the hotels could arrange training programs to teach their employees customer-oriented behaviors. By doing so, employees could improve their acting skills over time and consistently demonstrate customer-oriented behaviors. In future studies using longitudinal data would be a potential remedy for minimizing problems associated with the cross-sectional data. In future studies collecting data from multiple sources would also minimize problems emerging from self-report data. In closing, this study partially fills in the void in the services marketing literature by testing the aforementioned relationships using data gathered from frontline hotel employees in a developing sub-Saharan African country.
Keywords: Customer orientation; Hotel employees; Job resourcefulness; Nigeria; Performance